Answer:
see explanation
Explanation:
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.
Express in standard form, that is 6x² - 7x - 3
product = 6 × - 3 = - 18, sum = - 7
The factors are - 9 and + 2
Use these factors to split the middle term
6x² - 9x + 2x - 3 ( factor the first/second and third/fourth terms )
= 3x(2x - 3) + 1(2x - 3) ← factor out (2x - 3)
= (2x - 3)(3x + 1)
To obtain zeros equate to zero
(2x - 3)(3x + 1) = 0
Equate each factor to zero and solve for x
2x - 3 = 0 ⇒ x =
3x + 1 = 0 ⇒ x = -
--------------------------------------------------------------------------
The relationship between the zeros and the coefficients is
sum of zeros = -
and
product of zeros =
-
= -
and
-
=
× -
= -
and
=
= -
Verifying both relationships